Management of Charmakeela with Agnikarma and Kshara karma: A case report: Jayasuriya H.G.S.V.1, Wicramanayake W.A.A.P.2 and Peshala K.K.V.3 (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Agnikarma (therapeutic burn/cauterization) and Kshara are unique treatment modalities mentioned in Ayurveda under surgical methods. Acharya Susrutha has given a detailed description of Agnikarma. Agnikarma and Kshara show significant importance in Shalya tantra because of the nonoccurrence of diseases that are treated by Agnikarma. Charmakeela (warts) is a disease mentioned under Kshudra roga in the Ayurveda system and has various treatment principles including administration of Aushadha internally and external procedures like Raktamokshana, Ksharakarma, and Agnikarma. These treatment methods are minimal invasive procedures which has minimal scar formation, non-recurrence, and are found to be more beneficial in treating warts. This single case study is carried out for a 15-year-old patient who visited to Shalya clinic of Ayurveda National Hospital, Sri Lanka with multiple warts presented below the dorsal surface of left elbow joint for 06 months. He was treated with Agnikarma followed by application of Apamarga theekshna kshara. Post-operative dressing was done with Velmi churna. His wounds healed within 15 days with minimal scar. Through this case study it can be determined that Agnikarma combined with Kshara application is an effective treatment for the management of Charmakeela (warts).